Energy policy: strategies for uncertainty - Cook, P. Lesley; Surrey, A. J. (London: Martin Robertson, 1977)
This book is an outcome of the discussions that took place in 1974 during the course of a review of the work programme of the energy group in the Science Policy Research Unit at Sussex University. The general objective of the energy group is to contribute to thinking on policy issues, both by analyzing the energy outlook and by studying particular problems.
Includes bibliographical references: p. 229-234 and index.
ne 11/04/2018
Loans
Keywords: Energy Policy; Great Britain